(untitled) (AYUSHDHARA, 2018)
The word osteoporosis is derived from Greek word meaning porous bones, it is a progressive bone disease that is characterised by decrease in bone mass and destiny which can lead to a increased risk of fracture. In Ayurveda Osteoporosis is closely resembles with Asthidhatukshaya. A female patient aged 56 years was admitted in IPD of Rog nidan with complaints of pain in bilateral hip joint and knee joints, swelling, tenderness, restricted movements and general weakness since 8 months. It was diagnosed the case of osteoporosis. As per Acharya Charak, the remedial measures in the disorder of Asthi consist of the Panchkarma therapy, Basti and intake of bitter-medicated milk and ghee. So, in this study, Tiktaksheera Basti was selected for the management of Osteoporosis. The patient was admitted in IPD of hospital and treated with Ayurvedic medicine and Panchkarma therapies. Remarkable improvement was seen in all parameters i.e., pain, swelling and tenderness was reduced, range of movements increased and improvement in general health.